PENGARUH PERSEPSI KEMUDAHAN, PERSEPSI KEGUNAAN DAN PERSEPSI REPUTASI TERHADAP NIAT PENGGUNAAN APLIKASI INVESTASI BIBIT - Putra, I Putu Pradnyana Ekawan; Juliarsa, Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024DO - 10.24843/EEB.2024.v13.i06.p06, 2024)
The purpose of this research is to investigate the influence of perceived usefulness, perceived ease of use, and perceived reputation on the intention to use the Bibit investment application. The study was conducted on students from the 2019 to 2021 cohort of the Faculty of Economics and Business at Universitas Udayana. The data analysis technique used was multiple linear regression analysis. The approach used in this research is a quantitative approach in associative form. The data collection method in this research used a questionnaire distributed to student respondents at the Faculty of Economics and Business Universitas Udayana, users of the Bibit application created by PT. Bibit Maju Bersama. Distribution of the questionnaire was carried out boldly via Google Form. Based on the research results, all variables have a positive simultaneous effect, while the perceived reputation variable is not significant in partial effects. The research results indicate that perceived usefulness, perceived ease of use, and perceived reputation consistently have a positive effect on the intention to use the application. In future research, you should consider adding other variables that influence the intention to use the Bibit application, adding variations in the applications used, and further expanding the reach of respondents.